Foxtail millet supplementation improves glucose metabolism and gut microbiota in rats with high-fat diet/streptozotocin-induced diabetes - Xin Ren; Linxuan Wang; Zenglong Chen; Min Zhang; Dianzhi Hou; Yong Xue; Xianmin Diao; Ruihai Liu; Qun Shen (Food Science and Human Wellness)
Foxtail millet (FM) whole grain has received special attention in recent years. To confirm the hypoglycemic effects of FM, we investigated the effects of FM supplementation on glucose metabolism and gut microbiota in rats with high-fat diet/streptozotocin (HFD/STZ)-induced diabetes. Specifically, we fully assessed the blood biochemical profiles, pancreatic histopathology, insulin-glucagon immunofluorescence, short-chain fatty acids, and gut microbiota composition of rats with HFD/STZ-induced diabetes before and after FM supplementation. Results showed that both 30% and 48% FM supplementation significantly decreased concentrations of fasting blood glucose, 60-min blood glucose, and blood triglycerides (P < 0.05); additionally, 48% FM supplementation significantly improved blood glucose tolerance and insulin resistance (P < 0.05). However, FM supplementation could not effectively repair damage to β-cells over a short period of time. In addition, 4 weeks of 48% FM supplementation siginificantly increased the relative abundance of Bifidobacterium and concentration of butyrate, suggesting that the hypoglycemic effects of FM supplementation might be partially mediated by gut microbiota. Collectively, we found a dose-dependent relationship between FM supplementation and improvement of blood glucose metabolism, but did not find a synergistic effect between FM supplementation and metformin (Met) treatment. Our findings provide further support that consuming more whole-grain FM might be beneficial to individuals suffering from type 2 diabetes.